2019
DOI: 10.1186/s12913-019-4184-0
|View full text |Cite
|
Sign up to set email alerts
|

The willingness of patients to make the first visit to primary care institutions and its influencing factors in Beijing medical alliances: a comparative study of Beijing’s medical resource-rich and scarce regions

Abstract: Background To improve the efficiency of the use of medical resources, China has implemented medical alliances (MAs) to implement a hierarchical diagnosis and treatment system. The willingness to undertake a first visit to primary care institutions (PCIs) is an important indicator of the effect of this system. Beijing has also built MAs since 2013, but to date, there have been few studies on the first visit to PCIs in Beijing. The purpose of this study is to analyze patients’ willingness to make th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 15 publications
2
32
1
Order By: Relevance
“…Third, the development of medical alliances among healthcare providers are encouraged by the government. 54 The hospitals in the same medical alliance cooperate with each other rather than compete. Accounting for the potential limitations of objective competition measures, some studies alternatively employed perceived competition and suggested that competitive behaviors occur when the managers of organizations perceive a threat from competitors, regardless of the objective level of competition.…”
Section: Competition Measurementmentioning
confidence: 99%
“…Third, the development of medical alliances among healthcare providers are encouraged by the government. 54 The hospitals in the same medical alliance cooperate with each other rather than compete. Accounting for the potential limitations of objective competition measures, some studies alternatively employed perceived competition and suggested that competitive behaviors occur when the managers of organizations perceive a threat from competitors, regardless of the objective level of competition.…”
Section: Competition Measurementmentioning
confidence: 99%
“…urban areas, such as in Beijing [8] and Jiangsu Province [9], focus on the promotion of hierarchical diagnosis treatment system. Rural areas, such as Anhui Province [10], Y County, Hubei Province and Jiulongpo District, Chongqing Municipality [11], focus on the development of primary medical institutions by considering the county hospital as a bibcock.…”
Section: Many Provinces and Cities In China Have Explored Various Masmentioning
confidence: 99%
“…Many provinces and cities in China have explored various MAs modes in urban [11,12] and in rural areas [13,14]. The practice of MAs reforms in rural areas always considers county hospitals as leading hospitals and can be classified in two main types.…”
Section: Introductionmentioning
confidence: 99%